Elementary School Development Model: A Case Study - Farah, Rahmawati; Patang, Patang (Journal of Research and Innovation, 2023)
Abstract The purpose of this research is to 1) find out internal factors (strengths and weaknesses) and external factors (opportunities and threats) in improving the quality of SD Kemala Bhayangkari 01 Panaikang school. 2) To find out the model that needs to be done to improve the quality of SD Kemala Bhayangkari 01 Panaikang school based on SWOT analysis. The research approach used is qualitative and quantitative with the SWOT analysis method. Data collection techniques used are observation, interviews, questionnaires, and documentation. Data collection techniques used were descriptive analysis, SWOT matrix analysis, and IFE (internal factor evaluation) and EFE (external factor evaluation) matrix analysis. The results of the SWOT analysis for Kemala Bhayangkari Elementary School are in quadrant 1 where the IFE and EFE scores are (2.76 and 2.9). Which position supports the model in school development. Based on the results of the study, it can be concluded that the models used to improve the quality of SD Kemala Bhayangkari 01 Panaikang schools are the Reform school model and the Branding School model.